Analysis of Changes in the Position of the Tidal Front in the Waters at the Mouth of the Pangabuan River, Kuala Tungkal, Tanjung Jabung Barat District, Jambi - Amin Fatah; Elizal Elizal; Syahril Nedi (Tropical Marine Environmental Sciences, 2026)
This study aims to determine the distribution patterns of salinity and temperature, as well as changes in the position of the front in the waters at the mouth of the Pangabuan River in Kuala Tungkal, Jambi Province. This research was conducted in July 2022 in the waters of the Pangabuan River in Kuala Tungkal, Jambi Province. The analysis was conducted at the Oceanographic Physics Laboratory of the Department of Marine Science, Faculty of Fisheries and Marine Science, Riau University. There were two research stations: Station 1 was located in the river, and Station 2 was in the estuary. The tidal conditions in the waters of Kuala Tungkal are semi-diurnal, with two tides affecting the front in these waters. The highest tide occurs during the full moon (spring tide), reaching 3.1 m, while the lowest tide is 0.5 m. The tides strongly influence the position of the front; at high tide, the front is located deep within the river (2.45 km) from the estuary mouth, making it difficult to see and observe, while at low tide, the front is situated in front of the estuary mouth (1.4 km), making it easier to see and observe. The salinity distribution pattern in the front area shows a significant difference due to the mixing of two water bodies with different salinities: lower salinity comes from the river, and higher salinity from the sea. At high tide, salinity ranges from 20 ppm to 24.8 ppm; at low tide, from 17.3 ppm to 22.1 ppm. The highest temperature at high tide was 31.2°C and the lowest was 26.8°C; at low tide, the highest temperature was 31.6°C and the lowest was 27.6°C